PENGELOLAAN KONFLIK SOSIAL KEAGAMAAN DI PULAU LOMBOK - Lutfatul Azizah (Postgraduate State Islamic Institute (IAIN) Metro, 2021)
Religious conflict is a socio-religious dynamic that can strengthen the identity of a group or it can damage the religious social order of a community group. Conflict management determines how conflict becomes a procession of building a community or will damage the socio-religious order of a community. Conflict must be resolved, but what is far more important than conflict resolution is conflict management. Good conflict management is seen from community resilience to conflict. Lombok has a long history of socio-religious conflicts including a long history of the Ahmadiyah conflict and a long history of conflict with the largest religious organization on the island of Lombok. If we look at the two long conflicts that have occurred, the management of the conflict is quite interesting. Where one of them is an example of failure in conflict management and the other is an indicator of success in conflict management. Therefore, not only these 2 long conflicts but several conflicts also become a reference in this conflict management analysis.